Abundance of microplastic in different coastal areas using Phragmatopoma caudata (Kroyer in Morch, 1863) (Polychaeta: Sabellariidae) as an indicator - Menario, João Marcos Fausto Schuab (2022)
Plastic consists of a synthetic or semisynthetic polymer and its molecular structure is built of long repeating chemical units composed of hydrocarbons. Plastic materials degrade very slowly and plastic pollution has been considered an emerging problem in modern society. Microplastic (MP) particles are highlighted among the countless types of plastic debris disposed of in the ocean, once they can trap chemical pollutants and be mistaken as food by marine organisms, mainly filter-feeders and suspension feeders. The polychaete Phragmatopoma caudata (Kroyer in Morch, 1863) is a reef building Sabellariidae widely found on the brazilian coastline and has the ability to trap MP particles in their colonies structures. In order to evaluate MP pollution in different coastal areas, we collected 12 samples of water and 36 samples of P. caudata’s colonies in 12 sampling spots on the Espírito Santo (Brazil) coast divided into three regions (North, Central, and South). These samples were, processed, washed, and sieved, and the resulting product stored at a petri dish for further analysis. For sorting the MPs, a stereomicroscopic with an attached camera were used and all MPs were counted regarding their type (filament, fragment, and ‘other’) and color. Statistical analyses were performed using the GrahPad Prism software considering significant results p < 0.05. All 12 sampling spots were contaminated with MP, thus the investigated beaches had a MP pollution rate of 100%. The Central region showed the highest numbers of MP, followed by the North and the South regions respectively. This pattern of MP pollution in the Central region could be due to the high anthropic occupation, once it is where the capital and its metropolitan region are located, presenting more traffic of people. The Central region also holds two busy port complexes with intense ship traffic. The North region takes second place due to a specific sampling spot in the mouth of a big hydrographic basin, the Piraquê-Açú Basin. The South region holds the second more urbanized region of the Espírito Santo State, however, showed small numbers of MP, probably because two of the four sampling spots are slightly away from city impacts. Thus, microplastic pollution is indeed ubiquitous and widely found in coastal areas. Therefore, P. caudata colonies are a trustable indicator of MP presence in intertidal zones once they can trap plastic particles inside the colony structure. However, it is essential to investigate the mechanisms of MP trapping and how long they take to be absorbed from the water column into the colony, and how long they can remain trapped.